Reflections on the Regulation of European Securities Markets - Alexandre Lamfalussy (SUERF - The European Money and Finance Forum, 2001)
This Study is based on the 8th SUERF Lecture given by Alexandre Lamfalussy. Professor Lamfalussy has a long association with SUERF since its creation in 1963. In July 2000 the ECOFIN established the Committee of Wise Men on the Regulation of European Securities Markets under the chairmanship of Baron Alexandre Lamfalussy. In this SUERF Study the author first of all discusses the importance of the capital market in Europe and the mandate of the Committee and the way it conducted its investigation. The Study emphasises the shortcomings and weaknesses of the present system of regulation of European securities markets, and why these weaknesses have emerged. The paper also discusses the Committee's proposed remedies and some of the reactions to them. Professor Lamfalussy also considers some of the developments since the Committee published its report. Throughout the Study, the author emphasises the need for greater transparency and consultation in the regulatory process.
Keywords: 330; Wise Men Report; European Securities Market; EU Financial Regulation; Kapitalmarktrecht; Aktienmarkt; Finanzmarktaufsicht; EU-Staaten